Major arterial events in patients with chronic myeloid leukemia treated with tyrosine kinase inhibitors: a meta-analysis. Issue 6 (2nd June 2016) - Chai-Adisaksopha, Chatree; Lam, Wilson; Hillis, Christopher
Abstract: There is growing evidence that tyrosine kinase inhibitors (TKIs) may be associated with an increased risk of arterial events. We performed a meta-analysis to estimate the incidence of arterial events in patients with CML treated with TKIs. We identified 29 studies enrolling 15, 706 patients. The incidence rates of composite of major arterial events were 0.8 per 100 patient-years for non-TKI treatments, 1.1 per 100 patient-years for dasatinib, 0.1 per 100 patient-years for imatinib, 0.4 per 100 patient-years for bosutinib, 2.8 per 100 patient-years for nilotinib and 10.6 per 100 patient-years for ponatinib. The relative risk (RR) for nilotinib compared with imatinib suggests a significantly increased risk of the composite of major arterial events with nilotinib treatment (RR 5.3; 95%CI 3.0–9.3, p  < 0.001). This study demonstrates that, patients who received nilotinib or ponatinib had a greater number of major arterial events when compared to non-TKI-, imatinib-, dasatinib- and bosutinib-treated patients.